2016
DOI: 10.1111/jora.12246
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Abstention From Delinquency: Examining the Mediating Role of Time Spent With (Delinquent) Peers

Abstract: Research consistently identifies a group of adolescents who refrain from minor delinquency entirely. Known as abstainers, studying these adolescents is an underexplored approach to understanding adolescent minor delinquency. In this paper, we tested hypotheses regarding adolescent delinquency abstention derived from the developmental taxonomy model and social control theory in 497 adolescents (283 boys) aged 13-18 comparing three groups of adolescents: abstainers, experimenters, and a delinquent group. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The sample of respondents in this study is relatively well-functioning, indicated by a relatively high percentage of adolescents from high or medium SES households (89%). This percentage is significantly higher than in the Dutch population of adolescents [46], and is due to the study's full-family design. Another indication of a relatively well-functioning sample is the linear decrease of delinquent behavior over the course of adolescence.…”
Section: Limitationsmentioning
confidence: 59%
See 1 more Smart Citation
“…The sample of respondents in this study is relatively well-functioning, indicated by a relatively high percentage of adolescents from high or medium SES households (89%). This percentage is significantly higher than in the Dutch population of adolescents [46], and is due to the study's full-family design. Another indication of a relatively well-functioning sample is the linear decrease of delinquent behavior over the course of adolescence.…”
Section: Limitationsmentioning
confidence: 59%
“…This multi-informant design makes the data particularly suitable for testing our hypotheses, since we have direct measurements for the target respondent's delinquent behavior, as well as for their sibling's and best friend's delinquent behavior, together with detailed information on the respondent's relationship with parents and commitment to school. Adolescents who scored high on problem behavior in the last year of elementary school (based on teacher reports) were oversampled [46]. However, respondents came from relatively "well-functioning" and intact families, since 89% came from families with a medium or high socioeconomic status (SES) [23], and 95% of sibling pairs consisted of fully biologically related siblings.…”
Section: Datamentioning
confidence: 99%
“…Antisocial behaviors (ASB) consist of behaviors and attitudes that violate societal norms, including both aggressive (e.g., physical fighting and assault with a weapon) and nonaggressive rule breaking (e.g., theft, property destruction, and truancy) dimensions (Burt, 2009; Frick et al, 1993; Loeber & Schmaling, 1985). Although ASB are relatively common during adolescence (Moffitt, 1993), they are highly impairing as adolescents engaged in ASB are at increased risk for academic failure (Farrington, 1995), developing psychopathology (Castellani et al, 2014), and are more likely to engage in criminal activity in adulthood (Mercer, Keijers, Crocetti, Branje, & Meeus, 2016). Furthermore, ASB are a tremendous cost to society, including the increased economic burden they convey on our health care system, schools and communities, and the juvenile justice system (Foster & Jones, 2005).…”
mentioning
confidence: 99%
“…An explanation for this latter finding could be related to the perception of abstainers as well-adjusted adolescents (Brezina & Piquero, 2007) and later, well-adjusted adults (Moffitt et al, 2002). For example, parents of abstaining adolescents may not perceive the need to modulate their support according to anxiety levels as previous research has found adolescent abstainers to be high in conscientiousness (i.e., Mercer et al, 2016) and self-constraint (i.e., Boutwell & Beaver, 2008). Therefore, it is plausible that abstainers' parents may perceive them as more mature and in less need of explicit support as they enter emerging adulthood.…”
Section: Social Anxiety Delinquency and Relationship Qualitymentioning
confidence: 98%
“…In the protective perspective, the social inhibition characteristic of social anxiety may work as the protective mechanism against engaging in antisocial behaviors like delinquency (Lahey & Waldman, 2003;Pine, Cohen, Cohen, & Brook, 2000). More specifically, social anxiety may result in less time spent with peers or influence the types of activities adolescents engage in with their peers (e.g., going to the movies instead of going to unsupervised parties), leading to fewer opportunities for delinquency (e.g., Mercer, Keijsers, Crocetti, Branje, & Meeus, 2016;Nelemans et al, 2016). To further illustrate, social anxiety symptoms are thought to be associated with behavioral inhibition, risk-aversion, overregulation, and shy or submissive behavior (i.e., Gilbert, 2001).…”
Section: Social Anxiety and Delinquencymentioning
confidence: 99%